2019
DOI: 10.1186/s40880-019-0357-9
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic values of plasma Epstein‐Barr virus DNA for residual cervical lymphadenopathy in nasopharyngeal carcinoma patients: a retrospective study

Abstract: Background Currently, the diagnosis and treatment of nasopharyngeal carcinoma (NPC) patients with residual cervical lymphadenopathy following radical radiotherapy with or without chemotherapy are challenging. We investigated the prognosis of NPC patients with residual cervical lymphadenopathy and assessed the diagnostic and prognostic values of Epstein-Barr virus (EBV) DNA in these patients. Methods This study included 82 NPC patients who were diagnosed with suspected r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 51 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…Epstein–Barr virus (EBV), a large double-stranded DNA virus belonging to the γ-herpesvirus subfamily, causes latent infection of more than 95% of the adult population worldwide ( 1 , 2 ). As a widespread virus causing infectious mononucleosis during primary infection, EBV is also closely implicated in several malignancies in latent infection, including B-cell lymphomas, nasopharyngeal carcinoma (NPC) ( 3 , 4 , 5 ), EBV-associated gastric cancer, Burkitt's lymphoma, and Hodgkin's lymphoma ( 6 , 7 , 8 , 9 ). The viral oncogenic factors, such as RNA transcripts and proteins expressing during the latent or lytic phase have been reported to drive pathogenic processes ( 10 , 11 ).…”
mentioning
confidence: 99%
“…Epstein–Barr virus (EBV), a large double-stranded DNA virus belonging to the γ-herpesvirus subfamily, causes latent infection of more than 95% of the adult population worldwide ( 1 , 2 ). As a widespread virus causing infectious mononucleosis during primary infection, EBV is also closely implicated in several malignancies in latent infection, including B-cell lymphomas, nasopharyngeal carcinoma (NPC) ( 3 , 4 , 5 ), EBV-associated gastric cancer, Burkitt's lymphoma, and Hodgkin's lymphoma ( 6 , 7 , 8 , 9 ). The viral oncogenic factors, such as RNA transcripts and proteins expressing during the latent or lytic phase have been reported to drive pathogenic processes ( 10 , 11 ).…”
mentioning
confidence: 99%
“…The established nomogram demonstrated a high C-index in both the training and external validation cohorts, demonstrating its promising clinical significance. Pretreatment EBV DNA level had been demonstrated as an important biomarker for clinical management of NPC patients (18). Peng et al found that EBV DNA had an important prognostic value in predicting NPC patients' long-term survival after IMRT (19).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma EBV-DNA load has been well documented as an effective marker for distinguishing disease-associated EBV reactivation from the presence of EBV in benign B lymphocytes, as well as for diagnostic screening and monitoring of EBV-associated diseases such as lymphoma and nasopharyngeal carcinoma (NPC). [15][16][17][18][19][20] Especially in NPC patients, the quantification of plasma EBV-DNA can be used to screen for early asymptomatic NPC, 21,22 monitoring recurrence and predicting prognosis. 18 Little has been done to evaluate the role of plasma EBV-DNA load in the diagnosis and monitoring of GC.…”
Section: Introductionmentioning
confidence: 99%